IL-6 and MYC collaborate in plasma cell tumor formation in mice - Rutsch, Sebastian; Neppalli, Vishala T.; Shin, Dong-Mi; DuBois, Wendy; Morse, Herbert C., III; Goldschmidt, Hartmut; Janz, Siegfried (Blood, 2010)
Interleukin-6 (IL-6) plays a critical role in the natural history of human plasma cell neoplasms (PCNs), such as plasma cell myeloma and plasmacytoma (PCT). IL-6 is also at the center of neoplastic plasma cell transformation in BALB/c (C) mice carrying a transgene, H2-Ld-IL6, that encodes human IL-6 under control of the major histocompatibility complex H2-Ld promoter: strain C.H2-Ld-IL6. These mice are prone to PCT, but tumor development is incomplete with long latencies (∼ 40% PCT at 12 months of age). To generate a more robust mouse model of IL-6-dependent PCN, we intercrossed strain C.H2-Ld-IL6 with strains C.iMycEμ or C.iMycCα, 2 interrelated gene-insertion models of the chromosomal T(12;15) translocation causing deregulated expression of Myc in mouse PCT. Deregulation of MYC is also a prominent feature of human PCN. We found that double-transgenic C.H2-Ld-IL6/iMycEμ and C.H2-Ld-IL6/iMycCα mice develop PCT with full penetrance (100% tumor incidence) and short latencies (3-6 months). The mouse tumors mimic molecular hallmarks of their human tumor counterparts, including elevated IL-6/Stat3/Bcl-XL signaling. The newly developed mouse strains may provide a good preclinical research tool for the design and testing of new approaches to target IL-6 in treatment and prevention of human PCNs.
Prepublished online as Blood First Edition paper, December 17, 2009
Gesehen am 12.01.2022